2011
DOI: 10.1111/j.2042-7158.2011.01250.x
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic cannabinoid, CP55940, inhibits lipopolysaccharide-induced cytokine mRNA expression in a cannabinoid receptor-independent mechanism in rat cerebellar granule cells

Abstract: These results suggest that the synthetic cannabinoid CP55940 negatively modulates cytokine mRNA expression in cerebellar granule cells by a CB and GPR55 receptor-independent mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…PC12 cells express GPR55 mRNA, but not CB 1 or CB 2 mRNA, whereas rat cerebellar granule neurons express both GPR55 and CB 1 as we recently reported [27]. PC12 cells also expressed GPR55 protein as mouse 3T3-L1 adipocytes (Figure 1b).…”
Section: Resultssupporting
confidence: 66%
“…PC12 cells express GPR55 mRNA, but not CB 1 or CB 2 mRNA, whereas rat cerebellar granule neurons express both GPR55 and CB 1 as we recently reported [27]. PC12 cells also expressed GPR55 protein as mouse 3T3-L1 adipocytes (Figure 1b).…”
Section: Resultssupporting
confidence: 66%
“…Furthermore, CDB decreased TNF-a, IL-6 and chemokines (MCP-1 and MIP-2) in a murine model of acute lung injury (Ribeiro et al, 2012); synthetic cannabinoid inhibited TNF-a, IL-1b and IL-6 expression induced by lipopolysaccharide in rat cerebellar granule cells (Chiba et al, 2011). CBD reduced blood brain-barrier alterations and prevented endothelial inflammatory response in arteriolar and venular vasodilation, induced by lipopolysaccharide (Ruiz-Valdepeñ as et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Studies in rodent CNS also showed a wide expression Gpr55 mRNA in hippocampus, thalamus, forebrain, frontal cortex, hypothalamus, cerebellum and striatum (Chiba et al 2011, Sylantyev et al 2013, Wu et al 2013, Méndez-Díaz et al 2016, and GPR55 mRNA has also been found in monkey striatum (Martinez-Pinilla et al 2014). In addition, there is evidence that GPR55 is expressed at the protein level in the dorsal root ganglia neurons, where its activation enhances the excitability of sensory neurons (Lauckner et al 2008).…”
Section: Distribution Of Gpr55 In Humans and Rodentsmentioning
confidence: 94%